Measuring neutrophil functions might be a good predictive marker of overtraining in athletes - Yaegaki, M.; Umeda, T.; Takahashi, I.; Yamamoto, Y.; Kojima, A.; Tanabe, M.; Yamai, K.; Matsuzaka, M.; Sugawara, N.; Nakaji, S. (Luminescence, 2008)
In order to develop a predictive marker of overtraining in athletes, we examined the changes in neutrophil function [reactive oxygen species (ROS) production capability and phagocytic activity (PA)] for 10 male and 13 female judoists attending a training camp. Measurements were taken four times in total - immediately before and after a 2 h unified exercise loading (UEL) performed 1 day before (Pre-Camp) and the day after the 7 day training camp (Post-Camp). UEL-mediated aspartate aminotransferase was higher at Post-Camp than at Pre-Camp in females but not in males. Post-Camp leukocyte/neutrophil counts after the UEL significantly increased in females but not in males. The rate of change in C4 was significantly smaller in females than in males at Post-Camp. Only ROS significantly decreased without any compensation (increase in PA) being made at Post-Camp in females. In conclusion, this finding, namely that ROS significantly decreased only at Post-Camp without any compensatory mechanism (increase in PA), would suggest that the training camp imposed greater loading on females than males. This consideration was supported by the atypical aspartate aminotransferase, leukocyte/neutrophil counts and C4 findings which were seen at Post-Camp only in females. Therefore, regularly examining neutrophil functions such as ROS and PA might be a good preventative measure against overtraining in athletes participating in training camps.